Enhanced performance of solid oxide fuel cell by manipulating the orientation of cylindrical pores in anode substrate - Pan, W.; Lu, Z.; Chen, Kongfa; Zhang, Y.; Wei, Bo; Wang, Z.; Su, W. (Wiley - V C H Verlag GmbH & Co. KGaA, 2012)
Effect of the orientation of cylindrical pores within an anode has been studied on the performance of anode-supported solid oxide fuel cell (SOFC). Paper-fibers are used as pore-former and highly oriented cylindrical pores are formed within the anode prepared by uniaxial compaction. A thick anode brick is fabricated followed by cutting in different directions to obtain anode substrates with desirable orientation of pores. When the orientation of cylindrical pores is perpendicular to the anode surface, the gas transport is significantly improved so that the reduction rate of the NiO/YSZ anode is considerably accelerated and the cell concentration polarization is minimized. The corresponding single cell exhibits a maximum power density as high as 1.54 W cm–2 in hydrogen and 0.90 W cm–2 in nitrogen diluted methane at 800 °C. The result indicates that the output performance of anode-supported cells could be significantly improved by manipulating the orientation of pores.